Outcomes of robot-assisted partial nephrectomy for completely endophytic renal tumors: A multicenter analysis. Issue 5 (May 2021) - Carbonara, Umberto; Simone, Giuseppe; Minervini, Andrea; Sundaram, Chandru P.; Larcher, Alessandro; Lee, Jennifer; Checcucci, Enrico; Fiori, Cristian; Patel, Devin; Meagher, Margaret; Crocerossa, Fabio; Veccia, Alessandro; et al.
Abstract: Introduction: Multicenter retrospective analysis of robotic partial nephrectomy for completely endophytic renal tumors (i.e. 3 points for the 'E' domain of the R.E.N.A.L. nephrometry score) was performed. Materials and methods: Patients' demographics, tumor characteristics, perioperative, functional, pathological and oncological data were analyzed and compared with those of patients with exophytic and mesophytic masses (i.e. 1 and 2 points for the 'E' domain, respectively). Multivariable logistic regression analysis was used to assess variables for trifecta achievement (negative margin, no postoperative complications, and 90% estimated glomerular filtration rate [eGFR] recovery). Results: Overall, 147 patients were included in the study group. Patients with a completely endophytic mass had bigger tumors (mean 4.2 vs. 4.1 vs. 3.2 cm; p < 0.001) on preoperative imaging and higher overall R.E.N.A.L. score. There was no difference in mean operative time. Estimated blood loss was higher in the endophytic group (mean 177.75 vs. 185.5 vs. 130 ml; p = 0.001). Warm ischemia time was shorter for the exophytic group (median 16 vs. 21 vs. 22 min; p < 0.001). Postoperative complications were more frequent in patients with endophytic tumor (24.8% vs. 19.5% vs. 14.8%; p < 0.001). Six (4.5%) patients had positive surgical margins, there was no difference between groups. Trifecta was achieved in 44 patients in endophytic group (45.4 vs. 68.8 and 50.9%, p < 0.001). Multivariable analysis for trifecta revealed that clinical tumor size (odds ratio: 0.667, 95% confidence interval: 0.56–0.79, p < 0.001) was only significant predictor for trifecta achievement. Conclusions: Our findings confirm that RAPN in case of completely endophytic renal masses can be performed with acceptable outcomes in centers with significant robotic expertise.